Investigation of the effect of adalimumab on experimental brain injury in mice - Günal, Mehmet Yalçın; Çankaya, Seyda; Tönük, Şükrü Burak; Özdemir, Ekrem Musa; Sayın Şakul, Ayşe Arzu (My University, 2019)
Aim: We aimed to investigate the neuroprotective role of adalimumab based on the hypothesis that "TNF-alpha inhibitor adalimumab may affect inflammationrelated neuronal injury due to its anti-inflammatory effect". Methods: To investigate the effects of adalimumab, we induced brain injury in mice using a cold trauma model and evaluated the underlying cell survival/ death mechanisms via cresyl violet and calculated infarct/edema volume with image analyze system. Results: Although our data indicated a tendency to decreased infarct and edema volume, these findings are not significant statistically. Conclusion: To the best of our knowledge, this is the first study evaluating the neuroprotective effect of adalimumab on injured neurons.

Amaç: “TNF-alfa inhibitörü Adalimumab’ın, anti-inflamatuvar etkisi nedeniyle inflamasyonla ilişkili nöronal hasarı etkileyebileceği” hipotezine dayanarak adalimumab’ın nöroprotektif rolünü araştırmayı amaçladık. Metotlar: Adalimumab’ın etkilerini araştırmak için soğuk travma modelini kullanarak farelerde beyin hasarı oluşturduk ve krezil viyole boyasıyla hücre sağ-kalım/ölüm oranları ile görüntü analiz sistemi ile hesaplanan infarktüs/ödem hacmini değerlendirdik. Bulgular: Verilerimiz infarkt ve ödem hacminde azalma eğilimi göstermesine rağmen istatistiksel olarak anlamlı değildir. Sonuç: Bildiğimiz kadarıyla çalışmamız adalimumab’ın hasarlı nöronlar üzerindeki nöroprotektif etkisini değerlendiren ilk çalışmadır.
Adalimumab'ın farelerde deneysel beyin hasarına etkisinin araştırılması
Keywords: Brain Injury; Adalimumab; Neural Protection; Beyin Hasarı; Adalimumab; Nöroprotektif Etki